2020
DOI: 10.3390/su12145534
|View full text |Cite
|
Sign up to set email alerts
|

BIM and LCA Integration: A Systematic Literature Review

Abstract: To foster sustainable development, the environmental impacts of the construction sector need to be reduced substantially. Life cycle assessment (LCA) is the established methodology for the quantification of environmental impacts, and therefore has been increasingly applied to assess the environmental performance of buildings. By coupling LCAs with digital design tools, e.g., building information modeling (BIM), the identification of environmental hotspots and their mitigation is possible during the des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
93
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(95 citation statements)
references
References 65 publications
(112 reference statements)
0
93
0
2
Order By: Relevance
“…However, the BIM can be used only as a platform for BoQ, and thus a manual process of the evaluation can be used. Although this process is manual and time consuming, it is still the most common way of work as is shown in the aforementioned systematic literature review [29]. This process is possible; however, it leads to wide range of results [61,62].…”
Section: Limitations Of the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…However, the BIM can be used only as a platform for BoQ, and thus a manual process of the evaluation can be used. Although this process is manual and time consuming, it is still the most common way of work as is shown in the aforementioned systematic literature review [29]. This process is possible; however, it leads to wide range of results [61,62].…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…However, few studies [25,27] have focused on a specifically relevant workflow. The most recent systematic literature review of integrating BIM and LCA was published by Obrecht et al [29], which summarizes the topic from various perspectives and gives structured overview.…”
Section: Introductionmentioning
confidence: 99%
“…The use of BIM to conduct LCA can, for example, speed up the extraction of the bill of material quantities [29][30][31]. Existing reviews [30,32] show growing interest in the field, which is revealed, inter alia, by the increasing number of publications. Among existing BIM-based LCA studies, the comparison of different data sources at early and detailed stages of design in BIM has been addressed.…”
Section: Challenges In Data Sources Of Bim-based Lca In Building Desimentioning
confidence: 99%
“…BIM has important implications and advantages for the efficient design of structures and facilities [30][31][32][33]; thus, its inclusion in industrial engineering training can be of great assistance in the current conception and implementation of technical industrial projects. Despite the advantages of a multidisciplinary approach to BIM training and implementation [9,34] and the relationship between the product-process concept, development, and implementation of industrial engineering projects and the BIM approach [35][36][37][38][39][40][41][42][43][44][45][46][47], there are few reports on the introduction of BIM in industrial engineering degrees compared to the experience of BIM implementation in degrees related to architecture or construction engineering. The literature shows a general framework for the academic implementation of BIM in architecture, engineering, and construction [38,39] or a specific framework in architecture [40,41].…”
Section: Vdcmentioning
confidence: 99%
“…Nascimento et al proposed a methodology for the interdisciplinary management of construction projects by integrating BIM and lean thinking, which is widely used in industrial engineering projects, to improve the production planning and control of pipe-rack modules in an industrial facility [46]. From the perspective of sustainable development civil engineering projects, there are different approaches to integrating BIM and the LCA methodology used in industrial engineering projects [47]. All of these approaches could be implemented to include BIM in engineering project subjects.…”
Section: Vdcmentioning
confidence: 99%